(untitled) - Worthen, W. B. (New York, 2003)
In a series of essays, several of the most significant figures in the field present a wide-ranging interrogation of the practice of theatre history studies at the present time, raising questions of history and historiography; the bearing of national, sexual, and racial identity on the canons of theatre history; the limits of print and the history of non-textual forms of performance; the intersections between theatre and other forms of commodification; and even the work of performance at the borders of the human. Theorizing Practice is published in association with the Huntington Library.
Keywords: Theater,English drama; History,Congresses,History and criticism,Congresses; Great Britain